Uncertainty about the war in Ukraine: Measurement and effects on the German business cycle - Moritz Grebe; Sinem Kandemir; Peter Tillmann (Philipps-University Marburg, School of Business and Economics, 2023)
We assemble a data set of more that eight million German Twitter posts related to the war in Ukraine. Based on state-of-the-art methods of text analysis, we construct a daily index of uncertainty about the war as perceived by German Twitter. The approach also allows us to separate this index into uncertainty about sanctions against Russia, energy policy and other dimensions. We then estimate a VAR model with daily financial and macroeconomic data and identify an exogenous uncertainty shock. The increase in uncertainty has strong effects on financial markets and causes a significant decline in economic activity as well as an increase in expected inflation. We find the effects of uncertainty to be particularly strong in the first months of the war.
Keywords: D8; E3; G1; 330; war; Twitter; geopolitical risk; machine learning; business cycle